Single photovoltaic panel constant regulated voltage based on modified DC-DC buck-boost converter topology - Al Komar, Ro’ad Baladi; Rizqiawan, Arwindra (Institute of Advanced Engineering and Science, 2025)
This research proposes a single photovoltaic panel constant regulated voltage based on novel topology. A modified DC-DC buck-boost converter was chosen because characteristics of voltage boost and low input current ripple. A comprehensive analysis of the proposed converter cells was elaborated in this study. Furthermore, a control technique is designed for the proposed converter. A double-loop control method using proportional integral (PI) is employed in this research. The outer loop controls the output voltage, while the inner loop is used to control the inductor current. By employing double-loop control, the presence of ripple current and voltage can be reduced even further. Simulation and experimental results validate the converter’s effectiveness, demonstrating stable voltage output under varying input voltage (33-36 V) and load conditions, maintaining a 40 V output with an overshoot within ±5%. The results show that the modified buck-boost converter can achieve improved efficiency and ripple reduction compared to conventional models, making it a viable solution for renewable energy systems.